La competitività industriale nell’Unione Europea: un confronto tra l’Italia e i Paesi dell’Europa orientale - Ricci, Andrea (Argomenti, 2015)
During the crisis the Italian industry suffered a sharp contraction of output and employment. An opposite trend showed the New Member States (NMS) in Eastern Europe, to which continued the process of industrial relocation of Italian firms. The analysis of Unit Labor Cost (ULC), measured in Purchasing Power Parity, shows that this competitive gap stems from two factors. The first is of real character and relates to the low growth of labor productivity in the Italian industry. The second factor is of a monetary nature and relates to the undervaluation of the exchange rate of the currencies of the NMS with the euro. JEL Classification: F41; F14; F31; E24. Keywords: